2023
DOI: 10.1001/jamacardio.2022.5601
|View full text |Cite
|
Sign up to set email alerts
|

High-Sensitivity Troponin T and I Among Pregnant Women in the US—The National Health and Nutrition Examination Survey, 1999-2004

Abstract: This cross-sectional study investigates the expected physiologic concentrations of high-sensitivity cardiac troponin in normal pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 4 publications
2
7
0
Order By: Relevance
“…We agree with this finding but note that the work by Minhas et al did not include measurements of troponin in the peripartum period, which is the time when troponin levels are most often analyzed in clinical circumstances. We recruited 199 healthy women and analyzed consecutive measurements of hs-cTn T during and after pregnancy, including samples in the peripartum period .…”
supporting
confidence: 82%
See 2 more Smart Citations
“…We agree with this finding but note that the work by Minhas et al did not include measurements of troponin in the peripartum period, which is the time when troponin levels are most often analyzed in clinical circumstances. We recruited 199 healthy women and analyzed consecutive measurements of hs-cTn T during and after pregnancy, including samples in the peripartum period .…”
supporting
confidence: 82%
“…To the Editor We read with great interest the Research Letter by Minhas et al The authors conclude that “Pregnant women did not have elevated hs-cTn [high-sensitivity cardiac troponin] levels compared with nonpregnant women, …suggesting that pregnancy alone does not result in significant changes in troponin levels.”…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…All 4 cardiac chambers dilate slightly during pregnancy and left ventricular mass increases to accommodate the necessary increase in cardiac output. 28 In the postpartum period, individuals with a history of APO are at higher risk for heart failure, which may require unique considerations for screening, detection, and intervention (eg, echocardiography, laboratory-based biomarker levels (eg, BNP [brain-type natriuretic peptide], 171 high-sensitivity troponin 172 ). Data from a single center demonstrated that echocardiographic measurements 10 years after pregnancy were associated with adverse markers of cardiac remodeling in women with a history of HDP compared with normotensive pregnancies.…”
Section: Unanswered Questions and Future Directionsmentioning
confidence: 99%
“…In Reply We thank Furenäs and Dellborg for their letter and commentary on our article . Recent data show a concerning rise in maternal mortality in the US, with cardiovascular disease the leading cause of nonobstetric death .…”
mentioning
confidence: 92%